2023
DOI: 10.1002/jmv.28956
|View full text |Cite
|
Sign up to set email alerts
|

Can inspiratory muscle training benefit patients with COVID‐19? A systematic review and meta‐analysis

Yusha Chen,
Xuefeng Liu,
Zhaohui Tong

Abstract: The possible benefits of inspiratory muscle training (IMT) on mechanical and clinical outcomes in patients with Coronavirus disease‐2019 (COVID‐19) remain controversial. We conducted a meta‐analysis to evaluate the effect of IMT in the rehabilitation strategy of patients with COVID‐19. The Pubmed, Embase, Web of Science (WOS), and Cochrane Central Register of Controlled Trials (CENTRAL) were searched to identify trials evaluating the efficacy of IMT in the treatment of patients with COVID‐19. The primary outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
(89 reference statements)
0
5
0
Order By: Relevance
“…1 They found that IMT was associated with significant improvements in the change from baseline VO 2max , maximal inspiratory pressure (PI max ), 6-min walk distance, and forced expiratory volume in the first second predicted. 1 This manuscript presents a comprehensive analysis of the efficacy of IMT in the rehabilitation of COVID-19 patients.…”
Section: Inspiratory Muscle Training For Covid-19: Benefits Appear Pr...mentioning
confidence: 98%
See 4 more Smart Citations
“…1 They found that IMT was associated with significant improvements in the change from baseline VO 2max , maximal inspiratory pressure (PI max ), 6-min walk distance, and forced expiratory volume in the first second predicted. 1 This manuscript presents a comprehensive analysis of the efficacy of IMT in the rehabilitation of COVID-19 patients.…”
Section: Inspiratory Muscle Training For Covid-19: Benefits Appear Pr...mentioning
confidence: 98%
“…However, despite this encouraging finding, the findings should be interpreted with caution because of the high heterogeneity (I 2 > 50%) of the PI max outcome. 1 The observed variability in this outcome may be due to differences in study designs, such as varying control groups (e.g., no intervention, 3,4 sham IMT, 5 other forms of pulmonary rehabilitation [6][7][8] ), patient populations (i.e., hospitalized COVID-19 patients, 3,6,8 outpatients 7 or individuals with "long COVID" [3][4][5][6][7] ), and methodologies (including variations in IMT protocols, training devices, load intensity, session length and frequency, and overall program duration), [3][4][5][6][7][8] potentially impacting the generalizability of the findings.…”
Section: Inspiratory Muscle Training For Covid-19: Benefits Appear Pr...mentioning
confidence: 99%
See 3 more Smart Citations